Magnetic anisotropy of individually addressed spin states - L. C. J. M. Peters; P. C. M. Christianen; H. Engelkamp; G. C. Groenenboom; J. C. Maan; E. Kampert; P. T. Tinnemans; A. E. Rowan; U. Zeitler (Physical Review Research, 2021)
Controlling magnetic anisotropy is a key requirement for the fundamental understanding of molecular magnetism and is a prerequisite for numerous applications in magnetic storage, spintronics, and all-spin logic devices. In order to address the question of molecular magnetic anisotropy experimentally, we have synthesized single crystals of a molecular spin system containing four antiferromagnetically coupled s=5/2 manganese(II) ions. Using low-temperature cantilever magnetometry, we demonstrate the selective population of the S=0,1,...,10 spin states upon application of magnetic fields up to 33 T and map the magnetic anisotropy of each of these states. We observe a strong dependence of the shape and size of the magnetic anisotropy on the populated spin states, and, in particular, reveal an anisotropy reversal upon going from the lowest to the highest spin state.